2019
DOI: 10.1073/pnas.1813562116
|View full text |Cite
|
Sign up to set email alerts
|

Priming of microglia with IFN-γ slows neuronal gamma oscillations in situ

Abstract: Type II IFN (IFN-γ) is a proinflammatory T lymphocyte cytokine that serves in priming of microglia-resident CNS macrophagesduring the complex microglial activation process under pathological conditions. Priming generally permits an exaggerated microglial response to a secondary inflammatory stimulus. The impact of primed microglia on physiological neuronal function in intact cortical tissue (in situ) is widely unknown, however. We explored the effects of chronic IFN-γ exposure on microglia in hippocampal slice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 66 publications
10
110
0
Order By: Relevance
“…janelia.org) (Cembrowski et al, 2016) and found that both Ifngr1 and Ifngr2 gene transcripts are constitutively expressed in glutamatergic neurons of CA1-3 and dentate gyrus as well as parvalbumin (PV) or somatostatin (SST) expressing interneurons of mouse hippocampus. Furthermore, the presence of IFN-γ receptor in hippocampal microglia and astrocytes has been demonstrated, although the levels of expression differ depending on species and in vivo/in vitro conditions (Hashioka et al, 2010;Papageorgiou et al, 2016;Ta et al, 2019). Thus, the constitutive expression of IFN-γ receptors in several hippocampal cell There was no significant difference in mIPSC median amplitude (+TTX, 20.9 ± 1.36 pA, n = 11; IFN-γ + TTX, 24.34 ± 1.68 pA, n = 8; unpaired student t-test, p = .1281), or median rise time (10-90%) (+TTX, 2.42 ± 0.2 ms, n = 11; IFNγ + TTX, 1.93 ± 0.13 ms, n = 8; unpaired student ttest, p = .073), or median decay time (90-37%) (+TTX, 22.25 ± 1.05 ms, n = 11; IFN-γ + TTX, 20.23 ± 1.3 ms, n = 8; unpaired student t-test, p = .2369) in aCSF with IFN-γ (100 ng/ml) as compared to aCSF alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…janelia.org) (Cembrowski et al, 2016) and found that both Ifngr1 and Ifngr2 gene transcripts are constitutively expressed in glutamatergic neurons of CA1-3 and dentate gyrus as well as parvalbumin (PV) or somatostatin (SST) expressing interneurons of mouse hippocampus. Furthermore, the presence of IFN-γ receptor in hippocampal microglia and astrocytes has been demonstrated, although the levels of expression differ depending on species and in vivo/in vitro conditions (Hashioka et al, 2010;Papageorgiou et al, 2016;Ta et al, 2019). Thus, the constitutive expression of IFN-γ receptors in several hippocampal cell There was no significant difference in mIPSC median amplitude (+TTX, 20.9 ± 1.36 pA, n = 11; IFN-γ + TTX, 24.34 ± 1.68 pA, n = 8; unpaired student t-test, p = .1281), or median rise time (10-90%) (+TTX, 2.42 ± 0.2 ms, n = 11; IFNγ + TTX, 1.93 ± 0.13 ms, n = 8; unpaired student ttest, p = .073), or median decay time (90-37%) (+TTX, 22.25 ± 1.05 ms, n = 11; IFN-γ + TTX, 20.23 ± 1.3 ms, n = 8; unpaired student t-test, p = .2369) in aCSF with IFN-γ (100 ng/ml) as compared to aCSF alone.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ levels can increase under many pathological conditions particularly neuroinflammation (Ottum et al, 2015). In this study, we have pre-incubated the rat hippocampal slices with IFN-γ for 1-4 h at a concentration of 100 ng/ml, which has been shown to evoke maximal effects in microglia (Hausler et al, 2002;Ta et al, 2019). Notably, the actual IFN-γ concentration within the slices may be lower due to lack of blood flow, longer diffusion distance and limited extracellular space in hippocampal slices (McBain et al, 1990;Ta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations